Hand injuries in a human caused by a South American porcupine (ourico-cacheiro) - Haddad Júnior, Vidal [UNESP]; Vieira, R. B. [UNESP]; Cortes, C. R. (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2010)
Human injuries caused by South American porcupines (in Portuguese, ourico-cacheiro) are rare. This study reports severe hand injuries provoked by the body spines of the animal in a human and discusses the circumstances involved in the accident, with emphasis on environmental factors.
Keywords: South American porcupine; hand injuries; body spines; Brazil